Interaction With the Extracellular Matrix Triggers Calcium Signaling in Trypanosoma cruzi Prior to Cell Invasion - Manchola Varón, Nubia Carolina; dos Santos, Guilherme Rodrigo R. M.; Colli, Walter; Alves, Maria Julia M. (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi, the etiological agent of Chagas´ disease in humans, infects a wide variety of vertebrates. Trypomastigotes, the parasite infective forms, invade mammalian cells by a still poorly understood mechanism. Adhesion of trypomastigotes to the extracellular matrix (ECM) prior to cell invasion has been shown to be a relevant part of the process. Changes in phosphorylation, S-nitrosylation and nitration levels of proteins, in the late phase of the interaction (2 h), leading to reprogramming of both trypomastigotes metabolism and the DNA binding profile of modified histones, were described by our group. Here, the involvement of calcium signaling at a very early phase of parasite interaction with ECM is described. Increments in intracellular calcium concentrations during trypomastigotes - ECM interaction depends on Ca2+ uptake from the extracellular medium, since it is inhibited by EGTA or Nifedipine, an inhibitor of the sphingosine-dependent plasma membrane Ca2+ channel, but not by Vanadate, an inhibitor of the plasma membrane Ca2+-ATPase. Furthermore, Nifedipine inhibits the invasion of host cells by trypomastigotes in a dose-dependent manner, reaching 95% inhibition at 100 µM Nifedipine. These data indicate the importance of Ca2+ uptake from the medium and parasite-ECM interaction for host-cell invasion. Previous treatment of ECM with protease abolishes Ca2+ uptake, further reinforcing the possibility that these events may be connected. The mitochondrion plays a relevant role in Ca2+ homeostasis in trypomastigotes during their interaction with ECM, as shown by the increment of intracellular Ca2+ concentration in the presence of Antimycin A, in contrast to other calcium homeostasis disruptors, such as Cyclopiazonic acid for endoplasmic reticulum and Bafilomycin A for acidocalcisome. Total phosphatase activity in the parasite decreases in the presence of Nifedipine, EGTA and Okadaic acid, implying a role of calcium in the phosphorylation level of proteins that are interacting with ECM in trypomastigotes. In summary, we describe here the increment of Ca2+ at an early phase of the trypomastigotes interaction with ECM, implicating both a voltage gate channel in the influx of Ca2+ and the mitochondrion as the relevant organelle in Ca2+ homeostasis. The data unravel a complex sequence of events prior to host cell invasion itself.